Frequency Based Control of Antifouling Properties Using Graphene Nanoplatelet/Poly(Lactic-co-Glycolic Acid) Composite Films. Issue 11 (2nd November 2021) - Zamora-Ledezma, Camilo; Chicaiza-Zambrano, Alanis; Santiago Vispo, Nelson; Debut, Alexis; Vizuete, Karla; Guerrero, Víctor H.; Almeida, Cristina E.; Alexis, Frank
ABSTRACT: In this work, we report an approach to fabricate graphite nanoplatelets/poly(lactic-co-glycolic acid) composite films via drop casting. We tested their frequency-based control of antifouling properties on Escherichia coli bacteria TG1 strain (E. coli TG1), in the safe range of 5 MHz < f < 15 MHz. Scanning electron microscopy (SEM) showed that the average thickness of the composite coatings was 3.5 µm. Raman spectroscopy verified that the structure of the graphene flakes was conserved in the final nanocomposite. Bactericidal assessment was performed by measuring the optical density at 600 nm and the colony forming units (CFU). Our findings showed improved bacteria inhibition when exposed to alternating current frequencies (ACF) at 10 and 15 MHz. At these frequencies, bacteria had also suffered important damage, which was observed by SEM. Culture dynamics after 12 h of the frequency treatments exhibits a significant difference, associated to cell damage observed on bacteria subjected to a specific frequency. The anti-biofilm properties of alternating current frequency (ACV) stimulated GrFs/PLGA thin films underline the importance of the fabrication of novel nanocomposites for biomedical applications where biofilm proliferation is undesirable. Abbreviations : GrFs: graphite nanoplatelets; PLGA: poly(lactic-co-glycolic acid), E. Coli: Escherichia coli ; CFU: colony forming units; PEF: Pulsed Electric Field; OD: optical density; ES: electric stimulation; BC: bacteria control; BVF: variable frequency (BVF) treatments; ACVF: alternating current with variable frequency; EPS: extracellular polymeric substances; DMF: N, N-dimethylformamide; THF: tetrahydrofuran; ACF: alternating current frequencies; SEM: Scanning Electron Microscopy; TEM: Transmission Electron Microscopy. Graphical abstract: uf0001